Improving Audit Quality by Using Increased Auditor Ethics: A Qualitative Approach - Putri Nabila Felby Helvira; Maulana Yusup (Journal of Economics, Management, and Entrepreneurship, 2023)
The objective of this study is to investigate the ethical approaches employed by auditors in order to improve the overall quality of audits. The study utilizes a qualitative research methodology. The individuals chosen for interviews consist of the Head of Department, Auditors, as well as functional and non-structural officials from a regional examination office located in Bandung City. The results obtained from the conducted research demonstrate that Audit Ethics positively influence the quality of audits, which can be classified as either moderately satisfactory or not yet reaching optimal levels. Consequently, the structural authorities have enhanced the optimization of ethical strategies aimed at enhancing audit quality. However, they need to gain familiarity with the evaluation and measurement of auditors' performance and the conduct of such evaluations or measurements. To achieve proficiency and excellence, auditors must consistently execute their responsibilities in a professional manner and adhere to the prescribed code of ethics. This commitment ensures unbiased outcomes that furnish valuable information to the pertinent organization.